TRANSFORMATIONAL POTENTIAL OF A CLASSICAL UNIVERSITY MODEL - Kremеn Vasyl (The Modern Higher Education Review, 2017)
The given article is about the major challenges of university education in the ХХІ century. One of them is the innovative tendencies in modern civilization, which can be matched by a rapid spread of research universities. Another challenge is deep commercialization of university life in the context of globalization. Thus, entrepreneurial and corporate universities can become alternative forms of university life which are emerging in response to the above mentioned processes.